NIGERIA – CAMEROON SOUTHERN BOUNDARY CONFLICT, 1884-2002: TYPOLOGY, INTENSITY AND PROGRESSION - Ekong Demson; Nneka Sophie Amalu (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Since the introduction of European model of nation-states and boundaries in Africa (1884-1885), the history of the southern section of the Nigeria –Cameroon boundary had been a bellicose one until its resolution by the International Court of Justice in 2002. For over a century, the boundary between the two proximate neighbours had gone through several alignments and re-alignments. This paper identifies different typology of conflicts along the International divide, from colonial to post-colonial periods. These include territorial and positional disputes, functional, resource-based and frustration – aggression dimensions. It further examines the intensity and progression of the conflict between the two neighbouring African States, from the European scramble for territories, through independence, up to the International Court of Justice ruling in 2002.